2011
DOI: 10.1039/c0cc02249g
|View full text |Cite
|
Sign up to set email alerts
|

A tetraalkylated pyrene building block for the synthesis of pyrene-fused azaacenes with enhanced solubility

Abstract: The synthesis and characterisation of a soluble pyrene-fused tetraazaoctacene derivative has been achieved by developing a key pyrene-based building block with four solubilising groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…12 Despite the poor solubility of tetrabromopyrene, the selectivity is nearly perfect, providing tetra(n-hexyl)pyrene (1) cleanly and in high yield after crystallization on a decagram scale. 14 To demonstrate that this protocol is adaptable to polycyclic "island-terminated" haloalkyl segments, N-(4-chloro-butyl)carbazole 15 (2) was prepared, converted to the magnesium salt 3, and subjected to TBP under standard Kumada conditions (Scheme 1). 13 In comparison, the classic metal-catalyzed alkynylation/hydrogenation sequence returns lower yields and requires chromatography to obtain the products in reasonably pure form.…”
Section: Resultsmentioning
confidence: 99%
“…12 Despite the poor solubility of tetrabromopyrene, the selectivity is nearly perfect, providing tetra(n-hexyl)pyrene (1) cleanly and in high yield after crystallization on a decagram scale. 14 To demonstrate that this protocol is adaptable to polycyclic "island-terminated" haloalkyl segments, N-(4-chloro-butyl)carbazole 15 (2) was prepared, converted to the magnesium salt 3, and subjected to TBP under standard Kumada conditions (Scheme 1). 13 In comparison, the classic metal-catalyzed alkynylation/hydrogenation sequence returns lower yields and requires chromatography to obtain the products in reasonably pure form.…”
Section: Resultsmentioning
confidence: 99%
“…The intermediate 86 was subsequently bisalkylated to the dibutylated pyrene-imidazole 87 that was then deprotonatedp rior to the addition of [IrCl(cod)] (cod = cyclooctadiene) to afford complex 88.F urthermore, the COD ligands in complex 88 can be replaced by carbon monoxide in CH 2 Cl 2 ,a ffording the iridium-carbonyl complex 89. [77] As mentioned above,t he order of the oxidation and halogenation reaction, as well as the bromide reagent are critical for the preparation of pyrene-based precursors. In particular, the pyrene-based bisazolium complexes exhibited deep blue fluorescencep roperties, with emissions in the range of 370-450 nm, and quantum yields ranging from 0.29 to 0.41.…”
Section: Oxidation Of Pyrenesmentioning
confidence: 99%
“…[31,[77][78][79]93] For instance, the emission spectra of compound 113 showed ap eak centered at 478 nm with as houlder at 454 nm, and the emission bandso f114 display af eatureless emission band to the NIR region of 860 nm (Scheme 39). [31,[77][78][79]93] For instance, the emission spectra of compound 113 showed ap eak centered at 478 nm with as houlder at 454 nm, and the emission bandso f114 display af eatureless emission band to the NIR region of 860 nm (Scheme 39).…”
Section: Pyrene-based Materials With Luminiscencep Ropertiesmentioning
confidence: 99%
“…17 Recently, Mateo-Alonso et al reported an synthetic route for the preparation of 1,3,6,8-tetraoctylpyrene-4,5,9,10-tetraone by an indirect method. 18 Indeed, it is seemingly impossible that both bromination and oxidation of the pyrene is a straightforward and simple method. The main reason is that the solubility of the bromopyrene would decrease as the number of bromine atoms increase.…”
mentioning
confidence: 99%
“…Using 3 as a starting material, compounds 7 were synthesized by classical methods in two steps (condensation reaction of 3 with 1,2-diamine to afford 4 (83%) and Suzuki crosscoupling reaction of 4 with p-substituted phenylboronic acids gave 7 in good yields, Scheme 1). As a comparison, we also followed the Mateo-Alonso strategy, 18 i.e. oxidation of 7-tert-butyl-1,3-dimethoxyphenyl-pyrene (5) afforded the tetraketone 6 (28%), and then reacted with the 1,2-diamine in acetic acid solution yielded 7b (80%).…”
mentioning
confidence: 99%